Thermomechanical processing of micro-alloyed steel - Podaný, Pavel (Materiali in tehnologije, 2014)
The paper deals with the thermomechanical processing of low-carbon micro-alloyed steel processed by means of a physical simulation on a unique device for simulating a real forging process. The main goal of the experiment was to assess the mechanical and microstructural properties of steel after additions of various amounts of micro-alloying elements. Heats with additions of V, Nb, Ti and Zr were prepared. Different austenitization temperatures and different deformations were applied. Their influence on the microstructure and mechanical properties was evaluated.
Keywords: mikrolegirano jeklo; micro-alloyed steel; microstructure; mikrostruktura; termomehanska predelava; thermomechanical processing